Comparative ethnobotanical study in the North-East region of Morocco (Al Hoceima, Nador, and Jerada). Local ethnobotanical knowledge of Amazigh and Arabized provinces - Smaili, Halima; Mir, Fatima-Zahra; Merzouki, Abderrahmane (Ethnobotany Research and Applications, 2023)
Background: This study aims to compare the information recorded in the three provinces of Jerada, Nador, and Al Hoceima in the Northeastern part of Morocco, in order to evaluate variability of medicinal plant knowledge in these provinces. Methods: All the data were gathered through conducting open-ended semi-structured interviews with randomly selected individuals between 2017 and 2019. The study targeted people belonging to a specific ethnic category: The Berber tribes Aït Waryaghel in the province of Al Hoceima, the tribes Guelaya in the province of Nador, and the Arabs in the province of Jerada. Results: Information on 241 taxa were collected through ethnobotanical surveys conducted with a total of 1,177 persons across the three targeted provinces. In Jerada, 200 taxa were documented based on responses from 380 participants, of which 52% were women. In Al Hoceima, 179 taxa were identified through interactions with 410 persons, with 68% being men, while in Nador 131 taxa were recorded from interviews with 387 interviewees, with 53% being women. The analysis of the results revealed a total of 790 medicinal uses recorded across the provinces: 232 in the province of Al Hoceima, 172 in the province of Nador, and 386 therapeutic uses in the province of Jerada. Additionally, 474 other uses were recorded, with 166 in the province of Al Hoceima, 120 in the province of Nador, and 188 in the province of Jerada. Conclusions: Ethnicity indeed has an important role in the common knowledge of the population; it is even one of the imposing factors that forge it, making the comparison between different regions necessary in order to promote an adequate strategy to preserve biodiversity in a given region. Keywords: Ethnobotanical knowledge, Ethnicity, Medicinal plants, North-East Morocco.